A New Study on Tribological Performance of Phoenix Sp. Fiber-Reinforced Epoxy Composites - G. Rajeshkumar (Journal of Natural Fibers, 2021)
This paper presents the tribological performance of Phoenix sp. fiber-reinforced tribo-composites based on epoxy. The Phoenix sp. fiber-reinforced epoxy composites were fabricated by varying the fiber length (10, 20, and 30 mm) and fiber volume fraction (10%, 20%, 30%, 40%, and 50%) using the compression molding technique. The dry sliding wear test was conducted using pin-on-disk wear testing machine at different loads (10, 20, and 30 N), sliding speed (1, 2, and 3 m/s), and sliding distance (1, 2, and 3 km). The outcomes revealed that the presence of Phoenix sp. fibers in the composites improved the tribological performance of the neat epoxy. Moreover, the optimal fiber length and the fiber volume fraction were found to be 20 mm and 40%, respectively. The morphology of the worn surfaces of the samples was examined using a scanning electron microscope to study the wear mechanisms.